2023
DOI: 10.3390/polym15040814
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Nanofiber-Supported Cobalt–Nickel Nanoparticles as an Effective and Durable Catalyst for H2 Evolution via Sodium Borohydride Hydrolysis

Abstract: The successful support of bimetallic NiCo alloy nanoparticles (NPs) on poly(vinylidene fluoride-co-hexafluoropropylene) nanofibers (PVDF-HFP NFs) was achieved through electrospinning (ES) and in situ reduction. The synthesis and physicochemical characterization of Ni-Co@PVDF-HFP NFs with a range of bimetallic compositions (Ni1−xCox, x = 0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1) supported on PVDF-HFP NFs was undertaken. In comparison to their counterparts (Ni-PVDF-HFB and Co-PVDF-HFB), the bimetallic hybrid NF membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…While it has been demonstrated that precious metals (e.g., Pd, Ru, Pt, Rh, and their alloys) supported on different matrices exhibit outstanding performance for H 2 generation, their high cost and limited availability restrict their widespread usage [8][9][10][11]. To overcome this challenge, researchers are tirelessly working to develop a wide variety of catalysts based on non-precious metals, such as cobalt, nickel, and copper, and their alloys, which can catalyze the dehydrogenation of SBH and produce pure H 2 [12][13][14][15][16][17]. Copper-based catalysts are widely used because they are readily available and inexpensive [1].…”
Section: Introductionmentioning
confidence: 99%
“…While it has been demonstrated that precious metals (e.g., Pd, Ru, Pt, Rh, and their alloys) supported on different matrices exhibit outstanding performance for H 2 generation, their high cost and limited availability restrict their widespread usage [8][9][10][11]. To overcome this challenge, researchers are tirelessly working to develop a wide variety of catalysts based on non-precious metals, such as cobalt, nickel, and copper, and their alloys, which can catalyze the dehydrogenation of SBH and produce pure H 2 [12][13][14][15][16][17]. Copper-based catalysts are widely used because they are readily available and inexpensive [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their scarce availability and high cost, it has become of the utmost importance to investigate their substitute catalysts that are cheap and have the potentials to accelerate reaction rates while simultaneously reducing threshold activation energies. Thus, researchers are now focusing increasingly on abundant earth metals, such as transition metals like copper, cobalt, and nickel that are capable of catalyzing the dehydrogenation process of SBH [10][11][12].…”
Section: Introductionmentioning
confidence: 99%